Comorbid Depressive Symptoms and Chronic Medical Conditions Among US Chinese Older Adults. (12th August 2019) - Kong, Dexia; Solomon, Phyllis; Dong, XinQi
Abstract : OBJECTIVES: The prevalence and health consequences of comorbid depressive symptoms (DSs) and chronic medical conditions (CMCs) among older ethnic minority populations remain poorly understood. To bridge this gap, the present cross‐sectional study examined the prevalence of comorbid DS‐CMC and the association between such comorbidity and health services use among US Chinese older adults. DESIGN AND SETTING: Data were from the Population Study of Chinese Elderly in Chicago (N = 3157). The relationship between comorbid DS‐CMC and health service use (ie, emergency department [ED] visits and hospitalizations) was investigated by stratifying the sample into four groups: (1) neither DSs nor CMCs (ie, heart disease, stroke, cancer, high cholesterol, diabetes, high blood pressure, hip fraction, thyroid, and osteoarthritis); (2) DSs only; (3) CMCs only; and (4) comorbid DS‐CMC. Multivariate negative binomial regression models were conducted to determine the relationship between comorbid DS‐CMC and health service use. RESULTS: Participants were 73 years old on average. The prevalence of comorbid DSs ranged between 0.7% and 4.6% across various CMCs. The odds of DSs were at least twice as high among US Chinese older adults with CMCs than those without the various conditions. Compared with US Chinese older adults with neither DSs nor CMCs, those with comorbid DS‐CMC had more ED visits (rate ratio [RR] = 3.32; 95% confidence interval [CI] = 2.03‐5.42) and hospitalizations (RR = 3.12; 95% CI = 1.95‐4.97). CONCLUSION: Recognition and treatment of comorbid DS‐CMC warrant increased policy and clinical attention. The findings underscore the potential need to develop effective services targeting DSs among US Chinese older adults with CMCs. J Am Geriatr Soc 67:S545–S550, 2019.